2021
DOI: 10.1088/1748-605x/ac3147
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic 3D-printed PCL scaffold containing a high concentration carbonated-nanohydroxyapatite with immobilized-collagen for bone tissue engineering: enhanced bioactivity and physicomechanical characteristics

Abstract: A challenging approach of three-dimensional (3D)-biomimetic scaffold design for bone tissue engineering is to improve scaffold bioactivity and mechanical properties. We aimed to design and fabricate 3D-polycaprolactone (PCL)-based nanocomposite scaffold containing a high concentration homogeneously distributed carbonated-nanohydroxyapatite (C-nHA)-particles in combination with immobilized-collagen to mimic real bone properties. PCL-scaffolds without/with C-nHA at 30%, 45%, and 60% (wt/wt) were 3D-printed. PCL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…No impurity is observed in the XRD peaks. The most intense peak (101) was chosen to calculate the crystallite size according to Scherrer's Equation, 35 which gave an estimated average value of about 33 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No impurity is observed in the XRD peaks. The most intense peak (101) was chosen to calculate the crystallite size according to Scherrer's Equation, 35 which gave an estimated average value of about 33 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD diffraction peaks at around 2θ values of 32 , 34 , 36 , 48 , 57 , 63 , 66 , 68 , 69 , 73 , and 77 respectively correspond to the (100), ( 002), ( 101), ( 102), ( 110), ( 103), ( 200), ( 112), ( 201 impurity is observed in the XRD peaks. The most intense peak (101) was chosen to calculate the crystallite size according to Scherrer's Equation, 35 which gave an estimated average value of about 33 nm.…”
Section: Synthesis and Characterization Of Clay@ Znomentioning
confidence: 99%
“…Therefore, the increased Mepe expression might be related to the improved cell spreading on the OCP coating containing κ-carrageenan. ALP activity and matrix mineralization are important for bone regeneration ( Moghaddaszadeh et al, 2021 ). We found that κ-carrageenan in the OCP coating enhanced ALP activity and ALP protein in the short term (3, 7 days), as well as enhanced matrix mineralization in the long term (21 days) in pre-osteoblasts, suggesting stimulation of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Bone tissue engineering requires three-dimensional (3D)bioactive scaffolds mimicking bone in their structural, chemical, and mechanical properties in order to support cell adhesion, proliferation, and differentiation (Moghaddaszadeh et al, 2021). 3D printing is a favorable technology for producing bone scaffolds with controlled physical and mechanical properties, as well as a hierarchical structure analogous to the bone matrix (Entezari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%